Religie și istorie la poalele Vlădesei: Bologa - Pop, Diana (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
The Romanian countryside has always been a source of inspiration, an identity mark, a place in which tradition combines with history, religion and culture. With all the big changes that have occurred and still happen in the Romanian village, it will always represent a reference space for the Romanian culture itself. It will always be our birth- place, the place where the past meets the present to create the future. The countryside tells the story of a country, being a means of reference in the research of our national history; it describes the phenomenology of the people who live here and the country. In this article, I referred to one of the Romanian villages, Bologa, (Poieni commune, Cluj county), in which, Romanian history, religion, tradition and culture mingle harmoniously. Although the village, in time has transformed during the natural, permanent evolution, when you enter those places, The Roman Camp and The Medieval Fortress, they lead you to times long gone bye and they remind you of the stormy history of those places. The church, with its special aspect, built in black stone tells us too about the hard work and the desire of the people to keep it as a holy place in the heart of the village and its inhabitants. The water mill and the whirlpool, which is the only functioning one in the area, charm us making us feel as a fragile deck between past and present.